A tale of two New Zealand cities: Cycling to school among adolescents in Christchurch and Dunedin - Frater, J; Williams, J; Hopkins, D; Flaherty, C; Moore, A; Kingham, S; Kuijer, R; Mandic, S (Elsevier, 2017)
This study examined intrapersonal factors related to cycling to school among adolescents in two New Zealand cities based on the Theory of Planned Behaviour and the Prototype Willingness Model. Data were collected from 803 adolescents (Christchurch: n=373, Dunedin: n=430; age 13-18 years; living ≤4 km from school; non-boarders). Despite similar attitudes towards cycling to school, Dunedin adolescents had lower prevalence of cycling to school (2% versus 18% in Christchurch) and also scored lower for all measures of injunctive norm, descriptive norm, self-perceived cycling capability and autonomy, and behavioural intention with respect to cycling to school compared to their Christchurch counterparts. The dominant influence on the intention to cycle to school was subjective norm in Christchurch and attitude in Dunedin. Future initiatives for encouraging adolescents to cycle to school should consider the contributions of intrapersonal factors and the social needs of adolescents, and the need to increase adolescents’ cycle skills.